Faktor – Faktor Yang Berpengaruh Dalam Pemilihan Karir Sebagai Akuntan Publik Oleh Mahasiswa Program Studi Akuntansi Universitas Stikubank Semarang - Wida Alimah Azzah; Maryono Maryono (Jurnal Akuntansi Profesi, 2022)
Abstract The purpose of this paper is to examine the effect of financial rewards, labor market considerations, social values, personality, and work environment on career choices as public accountants by accounting students at Stikubank University, Semarang. The population in this study were students of the 2018 and 2019 accounting study programs at Stikubank University, Semarang. Sampling is using purposive sampling method and obtained a sample of 100 respondents. The data analysis technique used is multiple linear regression analysis. The results showed that financial rewards, labor market considerations, social values ​​and work environment had no influence on career choice as a public accountant by accounting students at Stikubank University, Semarang. Meanwhile, personality has a positive influence on career choice as a public accountant by students of the accounting study program at Stikubank University, Semarang. Keywords: Career Selection as a Public Accountant